Implementasi Pembelajaran Berdiferensiasi Pada Siswa Down Syndrome SD Muhammadiyah 1 Menganti - Trisna silvia; Muhammad Heri Prianto; Faridatul Ummah (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2023)
Education for children with special needs is education for children who have disabilities. Learning for children with special needs really requires separate strategies and techniques adapted to the needs of each child. Therefore, appropriate learning methods are needed to deliver learning material to children with special needs. In this research, the researcher attempted to analyze appropriate learning for children with special needs with a focus on the problem of how to implement differentiated learning for Down syndrome students at Muhammadiyah 1 Menganti Elementary School, obstacles in implementing differentiated learning for Down syndrome students at Muhammadiyah 1 Menganti Elementary School, efforts to overcome obstacles in implementing differentiated learning for Down syndrome students at SD Muhammadiyah 1 Menganti. This research uses a qualitative research method with a case study approach. The informants for this research were the principal and inclusion teacher at SD Muhammadiyah 1 Menganti. Data collection techniques use observation and interview methods. Data analysis in this research uses the Miles and Huberman model. Test the validity of the data by triangulation and adequacy of references. The result of this research is Differentiated Learning, namely a learning process that combines all differences with the aim of finding out about students' interests and talents and adjusting teaching to find out students' needs. Barriers to implementing differentiated learning for Down syndrome students at SD Muhammadiyah 1 Menganti are emotional, independence, non-expert teaching staff and lack of adequate infrastructure. Efforts to overcome obstacles in the implementation of differentiated learning for students with Down syndrome at SD Muhammadiyah 1 Menganti are by paying more attention, providing facilities for teaching staff or teachers accompanying PDBK students to take part in training, providing infrastructure and learning media.